Loss of Trust May Never Heal. Institutional Trust in Disaster Victims in a Long-Term Perspective: Associations With Social Support and Mental Health - Thoresen, Siri; Birkeland, Marianne S.; Wentzel-Larsen, Tore; Blix, Ines (Frontiers in Psychology, 2018)
Natural disasters, technological disasters, and terrorist attacks have an extensive aftermath, often involving society’s institutions such as the legal system and the police. Victims’ perceptions of institutional trustworthiness may impact their potential for healing. This cross-sectional study investigates institutional trust, health, and social support in victims of a disaster that occurred in 1990. We conducted face-to-face interviews with 184 survivors and bereaved, with a 60% response rate 26 years after the disaster. Levels of trust in the police and in the justice system were compared with general population data. We assessed the relationships between institutional trust and current psychological distress, social support, and life satisfaction. The levels of trust in the police and in the justice system were notably lower in survivors and bereaved than in the general population. Among the victims, low institutional trust was associated with more mental health problems, poorer social support, more barriers to seeking social support, and a lower life satisfaction. Lost trust in the aftermath of a disaster may perhaps never be restored and the lack of trust may act to strengthen or maintain health problems. An exclusively individualistic approach to trauma and disaster may miss out on the opportunities for promoting health and well-being that lies within the larger societal structures. Decision-makers should take this information into account, and acknowledge the potential long-term consequences of institutional performance in the aftermath of a disaster.